Perspectives on Exercise Intensity, Volume and Energy Expenditure in Habitual Cycle Commuting - Schantz, Peter; Salier Eriksson, Jane; Rosdahl, Hans (Frontiers in Sports and Active Living, 2020)
Background. Knowledge about physiology of cycle commuting combined with trip frequency and durations is necessary for understanding its character and potential influencing capacity. It needs to be investigated with validated methods. This is the first purpose of the study. On basis of the outcomes, the second purpose is to illuminate conceivable effects on health related outcomes. Methods. Ten male and ten female habitual commuter cyclists in their middle ages were studied at rest and with maximal exercise tests on a cycle ergometer and a treadmill in the laboratory. During their normal commute in the Stockholm County, Sweden, their oxygen uptake, heart rate, energy expenditure, ventilation, blood lactate, rated perceived exertion, number of stops, durations, route distances and cycling velocities were monitored with validated methods. The frequency of trips was self-reported. Results. The relative exercise intensity was 65 % of maximal oxygen uptake, and the energy consumption was 0.46 kcal per km and kg body weight for both sexes. Sex differences in MET-values (males, 8.7; females 7.4) mirrored higher levels of cycling speed (20 %), body weight (29 %), oxygen uptake (54 %) and ventilation (51 %) in males compared to females. The number of METhours per week during peak cycling season averaged 40 for the males and 28 for the females. It corresponded to a total energy expenditure of about 3500 and 1880 kcal for males and females, respectively. The number of trips per year was about 370, and the annual distance cycled was on the average 3500 km for males and 2300 for females. Conclusion. Cycle commuting is characterized by equal relative aerobic intensity levels and energy requirements for a given distance cycled for males and females. Based on an overall evaluation, it represents a lower range within the vigorous intensity category. The combined levels of oxygen uptake, durations and trip frequencies leads to high levels of METhours and energy expenditure in both males and females during both peak cycling season as well as over the year. Overall the study presents a novel basis for interpreting cycle commuting in relation to various health outcomes.